2014
DOI: 10.4236/ijmpcero.2014.32013
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Delivery Error Using a DICOM-RT Plan for Volumetric Modulated Arc Therapy

Abstract: The purpose of this study was to investigate the prediction of mechanical error using DICOM-RT plan parameters for volumetric modulated arc therapy (VMAT). We created plans for gantry rotation arcs of 360° and 180° (full-arc and half-arc VMAT) for six maxillary sinus cancer cases using a Monaco treatment planning system, and delivered the doses with a linear accelerator. We calculated DICOM-RT plan parameters, including gantry, multileaf collimator (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Miura et al also showed that gamma passing rates are correlated with MLC leaf velocity, indicating that errors in MLC positions due to large velocities may have negative effects on dosimetric accuracy (Miura et al 2014b). Furthermore, it has been shown that constraining the millimeters traveled per leaf per MU improves the delivery accuracy of the treatment plan (Chen et al 2011, Miura et al 2014a.…”
Section: Introductionmentioning
confidence: 99%
“…Miura et al also showed that gamma passing rates are correlated with MLC leaf velocity, indicating that errors in MLC positions due to large velocities may have negative effects on dosimetric accuracy (Miura et al 2014b). Furthermore, it has been shown that constraining the millimeters traveled per leaf per MU improves the delivery accuracy of the treatment plan (Chen et al 2011, Miura et al 2014a.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of IMRT and VMAT plans leads to a decreased gamma passing rate in dosimetric results [6] [7] [11]. Our previous study investigated dosimetry measurements of VMAT plan parameters using DICOM-RT verification and compared them to mechanical dose errors using a log file [13]. Despite the necessity of assessing VMAT plan complexity to ensure secure treatment planning, however, methods for quantitative assessment of VMAT plan complexity are still lacking.…”
Section: Introductionmentioning
confidence: 99%